1978
DOI: 10.1001/archderm.114.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous signs of spinal dysraphism. Report of a patient with a tail-like lipoma and review of 200 cases in the literature

Abstract: The term "spinal dysraphism" was coined in 1940 by Dr Lichtenstein to designate incomplete fusion or malformations of structures in the dorsal midline of the back, particularly congenital abnormalities of the vertebral column and spinal cord. Raphes develop on the face and head, brancheal arches, sternum, and spinal column. When dysraphism occurs in these sites, failure of closure of fontanelles, cleft lip and palate, brancheal cysts, and abnormalities of the ribs and spine result. A review of 200 cases of occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 16 publications
2
69
0
Order By: Relevance
“…In a report of 200 cases by Tavafoghi et al 9 , the spinal dysraphism was shown to be a condition associated with cutaneous signs in more than 50% of instances. In our case, no other accompanying anomalies except for slight hypertrichosis drew attention on lumbar region.…”
Section: Discussionmentioning
confidence: 96%
“…In a report of 200 cases by Tavafoghi et al 9 , the spinal dysraphism was shown to be a condition associated with cutaneous signs in more than 50% of instances. In our case, no other accompanying anomalies except for slight hypertrichosis drew attention on lumbar region.…”
Section: Discussionmentioning
confidence: 96%
“…Sacral hypertrichosis is also known as faun tail naevus, and this is the most common skin lesion that is evident at birth 11 , as was seen in our patient. Hairy patches are most frequently associated with tethered cord and diastematomyelia 12 . Although our case demonstrated no underlying neurologic problem associated with his localized hypertrichosis, accurate screening modalities such as MRI are necessary to detect any underlying dysraphic anomalies and to prevent the occurrence or progression of the neurologic deficit by timely intervention before neurological damage has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…They may be in the midline or off to one side, and rarely is there a history of family members born with a tail. There is a high rate of associated abnormalities of the skin, including hypertrichosis, hyperpigmentation, dermal sinus tracts and hemangiomas [16]. Lu et al [3]reviewed the literature on human tails between 1960 and 1997 and found 59 cases.…”
Section: Discussionmentioning
confidence: 99%